Can central banks successfully lean against global headwinds? - Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Despite expansionary central bank action, inflation remains low in the euro area. How much can we expect from the additional stimulus in face of anaemic global growth and declining oil prices? More generally, have central banks lost the ability to steer inflation in a globalised world where external factors have powerful effects on domestic inflation? This roundup summarises the evidence in the literature and concludes that central banks retain influence on domestic inflation.
Keywords: 330